Naso-orbicular tissue necrosis by Streptococcus parasanguis in a patient with Fanconi anemia: Clinical and laboratory aspects - Fernandes Gomes, Mônica [UNESP]; Santos Teixeira, Raquel Teodoro [UNESP]; Plens, Glauco; Silva, Marcelo Miloni; Pontes, Elitânia Marinho; Rocha, João Carlos da [UNESP] (My University, 2004)
Fanconi anemia (FA) is a rare autosomal recessive disorder, characterized by pancytopenia and progressive hypoplasia of the bone marrow. A 23-year-old woman with FA showed severe pancytopenia and developed an abscess on the infraorbicular region on the right side of the face that progressed to phlegmon and caused tissue necrosis of the nostrils, nasal septum, nasal fossa, and posterior orbital region. Laboratory examination showed Streptococcus parasanguis as the etiologic agent of the phlegmon. Supportive treatment was recommended due to donor incompatibility for bone marrow transplant. The intraoral examination showed spontaneous gingival bleeding, edema of the interdental papillae, hematomas on the superior and inferior lips, bacterial and fungal infections, and adequate oral hygiene. The patient was treated with the administration of an antibiotic (imipenem), an antifungal (amphotericin B), and mouth washing with antiseptic solutions. Periodontal prophylaxis and orientation to and control of oral hygiene and diet were also used during the remission period. For functional and esthetic rehabilitation of the alar regions and nasal dorsum, an acrylic resin nasal prosthesis was made, supported by a spectacle frame.
Keywords: 3788del; FANCA gene; Fanconi anemia; Infection; Pancytopenia; Streptococcus parasanguis; Tissue necrosis; amphotericin B; antiinfective agent; imipenem; abscess; adult; bacterial infection; bone marrow transplantation; case report; clinical feature; edema; female; gingiva bleeding; hematoma; human; laboratory test; mouth examination; mouth hygiene; mycosis; nose cavity; nose septum; pancytopenia; phlegmon; Streptococcus infection; tissue necrosis; Acrylic Resins; Adult; Anti-Bacterial Agents; Cellulitis; Fanconi Anemia; Female; Humans; Necrosis; Nose; Nose Diseases; Orbital Diseases; Prostheses and Implants; Streptococcal Infections; Streptococcus